Virtualization of the IT system implementation process on the example of Protetic4You - Chomiak-Orsa, Iwona; Gryncewicz, Wiesława; Leszczyńska, Maja (Wirtualizacja procesu wdrożenia na przykładzie oprogramowania Protetic4You, 2011)
Virtualization of IT system implementation processes is now possible in small and micro companies. They are characterized by relative simplicity and marked recurrence of business processes. Popularity of such approach to implementation is largely due to the wide availability of IT solutions offering remote administration of authorized IT resources. Virtualform of implementation offers significant reduction of both cost and time, compared with traditional approach. The aim of this paper is to offer an insight into potential of virtualization of business processes through the evaluation of the IT system implementation process on the example of Protetic4You
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 205, s. 73-83
Keywords: virtualization; IT system; implementation process; small and micro companies